2019
DOI: 10.3390/ijerph16071140
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Temperature and Solar Radiation as Predictors of Bipolar Patient Admission in an Emergency Psychiatric Ward

Abstract: Environmental variables can regulate behavior in healthy subjects. Recently, some authors investigated the role of meteorological variables in bipolar patients with an impact on both the onset and course of bipolar disorder (BD). The aim of this study was to investigate the impact of meteorological variables and other indexes in bipolar hospitalized patients. We examined all patients admitted to the Psychiatric Inpatient Unit of San Luigi Gonzaga Hospital, Orbassano (Turin, Italy) from September 2013 to August… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Studies of the association between hospital admissions of BD patients and solar radiation, maximum temperature, and seasonal patterns in photoperiod have shown that manic episodes tend to peak during spring and summer months, with a minor peak in autumn (Aguglia et al, 2017(Aguglia et al, , 2018(Aguglia et al, , 2019. In contrast, depressive episodes displayed peaks in early winter and less frequently in summer, with mixed episodes peaking in early spring or summer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the association between hospital admissions of BD patients and solar radiation, maximum temperature, and seasonal patterns in photoperiod have shown that manic episodes tend to peak during spring and summer months, with a minor peak in autumn (Aguglia et al, 2017(Aguglia et al, , 2018(Aguglia et al, , 2019. In contrast, depressive episodes displayed peaks in early winter and less frequently in summer, with mixed episodes peaking in early spring or summer.…”
mentioning
confidence: 99%
“…Taken together, the compelling evidence in support of circadian disturbances in BD may also feed into seasonal influences relating to the onset of symptoms of bipolar mania or bipolar depression. Studies of the association between hospital admissions of BD patients and solar radiation, maximum temperature, and seasonal patterns in photoperiod have shown that manic episodes tend to peak during spring and summer months, with a minor peak in autumn (Aguglia et al., 2017 , 2018 , 2019 ). In contrast, depressive episodes displayed peaks in early winter and less frequently in summer, with mixed episodes peaking in early spring or summer.…”
mentioning
confidence: 99%
“…In Germany and Greece, increased solar insolation may precede suicidal acts (Müller et al 2011 ; Papadopoulos et al 2005 ). In Italy, higher solar radiation was associated with an increase in patients admitted to an emergency psychiatric unit with a primary diagnosis of bipolar disorder (Aguglia et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sherbakov et al (2018) concluded admissions for mental health were significantly increased with higher temperatures in California, US. The study in Italy showed temperature and humidex index were significantly associated with admission in an emergency psychiatric ward, and maximum temperature and solar radiation were associated with bipolar disorder ( Aguglia et al, 2020 , Aguglia et al, 2019a ). Significantly increased risk of the admission counts for schizophrenia was observed at a temperature range of 3.2 °C (10th percentile), and 12.1 °C (99th percentile) in Taiwan, China ( Sung et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%